The Essence of Mattompang Arajang Tradition in Sociocultural Perspective in Bone Regency Society - Hamida, Nurainun; Jayadi, Karta; Idrus, Idham Irwansyah (Jurnal Pendidikan Sosiologi dan Humaniora, 2025)
This study aims to; 1) Describe the process/stages of the Mattompang Arajang tradition in Bone Regency. 2) Analyze the meaning of Mattompang Arajang culture in the socio-cultural life of the people in Bone Regency. 3) Analyze the impact of the Mattompang Arajang tradition in the life of the Bugis Bone community. The type of research used is qualitative research with a descriptive approach, the author wants to understand how humans together create the reality of their social groups, organizations, and cultures. The number of informants consists of 7 people, with the following criteria; cultural figures of Bone Regency and the people of Bone Regency. Data collection techniques used are observation, documentation, and interviews. The results of the study show that: 1) The mattompang arajang tradition procession in Bone Regency is; a) malekke toja, is the process of moving or taking water from a holy spring accompanied by the sound of traditional music, b) mappaota is the process of presenting betel as a symbol that the mattompang arajang tradition will soon begin, c) matteddu arajang is the process of waking up heirlooms with a ceremony accompanied by music, d) mattompang arajang/masossoro, is the process of purifying heirlooms accompanied by drums and dance during the cleaning process, and e) mappatinro arajang is the process of putting heirlooms back to sleep by reciting prayers known as mamemmeng 2) The meaning of the mattompang arajang tradition in Bone Regency is; a) the magical meaning b) the meaning of cleansing/purifying, c) the meaning of friendship and mercies and d) the meaning of cultural preservation 3) The impact of the Mattompang Arajang tradition in people's lives is the social impact as the Mattompang Arajang tradition is a place to strengthen relations between groups and the cultural impact is one way of introducing traditional values to the younger generation as cultural preservation.